Structural changes of the microplankton community following a pulse of inorganic nitrogen in a eutrophic river. (7th November 2019) - Kleinteich, Julia; Hilt, Sabine; Hoppe, Andreas; Zarfl, Christiane
Abstract: Global change will increase the number and severity of extreme events resulting in strongly pulsed nutrient loading to rivers. Recent studies indicate the potential for rapid plankton shifts as short‐term response to storm events and highlight the need for high‐frequency methods to understand these complex processes. Here, we studied the effects of a strong short‐term pulse of ammonium nitrate in a eutrophic temperate river that elevated nitrate‐N concentrations from 3.1 to 10–55 mg L −1 . An intense phytoplankton bloom increased chlorophyll  a concentrations from below 10 μ g L −1 to over 140  μ g L −1 despite of high background N concentrations and followed the N‐pulse downstream. High‐throughput sequencing revealed the temporal dynamics of the bacterial (16S rRNA gene) and microeukaryotic (18S rRNA gene) community throughout the event. Bacterial and microeukaryotic community richness was reduced, and community composition changed significantly during the bloom. Few microeukaryote taxa (e.g., Cyclotella meneghiniana, Chlamydomonas ) dominated the bloom and replaced the rich summer phytoplankton community. Long‐term monitoring data (2008–2016) using classical microscope analyses showed that seasonal shifts in phytoplankton community composition were linked to physical parameters and nutrient availability with P‐limitation observed in spring but not in summer. We conclude that a disturbance in abiotic and biotic control factors, such as caused by a nutrient pulse, can induce structural shifts in the microplankton community leading to a phytoplankton bloom, even in eutrophic waters.